POLIMORFISME GENA METILEN TETRAHIDROFOLAT REDUKTASE, PROTOMBIIN, FAKTOR V LEIDEN, INTERSELULAR ADHESI MATRIKS-1, NITRIT OKSID SINTASE-3, SEBAGAI FAKTOR RISIKO GASTROSISIS - , Akhmad Makhmudi, dr.,SpB.,Sp.BA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction: Gastroschisis is a birth defect involving extrusion of fetal intestines through a defect in the right side umbilical abdominal wall. Interruption of the blood flow in the vascular plexus that will form the right vitelline arteries (inferior omphalomesenteric artery) has been proposed as the mechanism by which Gastroschisis occurs. We hypothesized that affected fetuses have a genetic predisposition to arterial or venous thromboembolism, defect in the integrity of the dermis and the angiogenesis. Patients and Methods: In a case-control study of 39 cases of Gastroschisis and 39 ethnic-matched controls in Indonesian population, we analyzed 5 single nucleotide polymorphisms (SNPs) of MTHFR c.677C>T, Prothrombin c.20210G>A, Factor V Leiden c.1691G>A, ICAM1 c.1462A>G, and NOS3 c.894G>T using Polymerase Chain Reaction â Restriction Fragment Length Polymorphism technique. For control group of each study, the observed genotype frequencies of 5 SNPs were assessed for Hardyâ Weinberg equilibrium using Ï2 test. The strength of association was accessed by calculating odds ratios (ORs) and 95% confidence intervals (CIs). The pooled ORs were performed for allelic genetic model (T vs. C, A vs. G, A vs. G, A vs. G, and T vs. G), dominant model (TT+CT vs. CC, AA+AG vs. GG, AA+AG vs. GG, AA+AG vs. GG, and TT+GT vs. GG), and recessive model (TT vs. CT+CC, AA vs. AG+GG, AA vs. AG+GG, AA vs. AG+GG, and TT vs. GT+GG), respectively. Results: TT genotype of MTHFR c.677C>T showed marginally significant association with Gastroschisis at p-value of 0.09 (OR=12.57